Research Design of the Main Parameters of the Quarry (Texas Journal of Multidisciplinary Studies, 2022)
The article deals with the study of the design of the main parameters of a quarry. The correct choice of the depth and contours of the quarry is described, since they determine the volumes of minerals involved in the development.